Self-esteem and alcohol consumption in high school adolescents of Ciudad del Carmen, Campeche - Telumbre-Terrero, Juan Yovani (Universidad de Sonora, 2019)
Introduction: Adolescents go through a stage of biological, psychological, and social changes that may be conditioning factors in the development of harmful behaviors such as the use and/or abuse of alcohol. Objective: Establish the association between self-esteem and the consumption of alcohol by adolescents. Methodology: Correlational descriptive research was conducted on 191 high school adolescents of Ciudad del Carmen, Campeche, Mexico. The Alcohol Use Disorders Identification Test (AUDIT) and the Rosenberg Self-Esteem Scale were used. Results: The type of consumption of the dependent (35.4%) followed by the sensible (34.1%) prevails; by gender, a dependent consumption prevails in males (39.4%), while a sensible consumption prevails in women (38.8%). According to the AUDIT score (r = -0.425, p = 0.042), a negative relationship was established between self-esteem and alcohol consumption. Conclusion: The intake of alcoholic beverages represents a growing health concern that may cause a variety of adverse health conditions in adolescents, in addition to being associated with psychological variables such as self-esteem, which plays a key role in the acquisition or modification of healthy or unhealthy habits, and therefore constitutes a protective variable against alcohol consumption.